Risk Evaluation of Multi-objective Dispatching Scheme for Shaanxi Hanjiang-to-Weihe River Diversion Project - GAO Chen; REN Mengzhi; LIU Dengfeng; HUANG Qiang (Renmin Zhujiang)
Hanjiang-to-Weihe River Diversion Project in Shanxi Province is aninter-basin water diversion project to solve the water shortage in Guanzhong andnorthern Shaanxi provinces. In order to give full play to the benefits of theproject, it is necessary to evaluate the risk of reservoir group operation scheme.Under two operation modes for giving priority to water supply for the HuangjinxiaReservoir and the Sanhekou Reservoir, this paper establishes the risk evaluationindex system of multi-objective operation of Hanjiang-to-Weihe Diversion Projectbased on the objective of operation, assigns the weight to each index by AHP, andobtains the risk value of each operation scheme by TOPSIS (Technique for OrderPreference by Similarity to Ideal Solution) method, which provides technicalsupport for the final decision. After evaluation of operation schemes under twoprior water supply modes, respectively, the results show that the comprehensiverisk of the scheme is mainly affected by insufficient indicators of water supplyrisk; the comprehensive risk rate of the two schemes under mode 1 of prior watersupply for Huangjinxia Reservoir is lower than that of the two schemes under mode2 of prior water supply for Sanhekou Reservoir, and the two schemes under mode 1have better water supply recovery than that under mode 2. Therefore, two schemesunder the mode 1 are recommended.